Environmentally Friendly Concept in Spatial Regulation - Taryono, T (Forum Geografi, 1991)
Spatial order of a region include purpose of structure and interrelatedness of spatial order which as a unity of development mechanism. Spatial order canât be part from law basic that is UUDâ45 and GBHN, in order to the management can be integrated and keep the environment. Spatial order also take note of physical factor and non physical factor. Physical factor consist of soil, water, flora, and fauna. Non physical factors consist of environment, social, economic, and soon. The principle of arrangement of spatial order in a region include national region, regional and local, and a region as an administrative baoundary, that is local government authority, like province, district, subdistrict, and village. The effort for spatial ordering of the environment, for example ordering resource, arrangement of allocation and location, arrangement of environmental aestheticÂ  and arrangement of environmental quality.